Carboxylic acids produced by anaerobic digestion: sugarcane and cassava - Tello Idme, Fredy Alex; da Fonseca-Zang, Warde Antonieta; Da Fonseca, Regina Célia Bueno; Leandro, Wilson Mozena; Bueno da Fonseca, Cláudia Adriana; dos Santos, Alex Mota (Revista Gestão & Sustentabilidade, 2025)
This research investigated the production of carboxylic acids (CA) by anaerobic digestion (AD) using organic agro-industrial waste from Brazil. Two experimental routes were tested: Route A for biogas production with active archaea and Route B for CA production with inhibited archaea, using different pH conditions to suppress methanogenesis. The residues analyzed were sugarcane filter cake and cassava peel processing residues, with bovine manure as inoculum. The concentration of short-chain carboxylic acids (SCCA) was evaluated over 21 days using gas chromatography with flame ionization detection (FID). The most significant values were observed for acetic acid (43%) and butyric acid (40%) contents, increasing on day 4 of the experiment from route A to route B in the case of acetic acid from 51 mg/gMSO to 294 mg/gMSO, and in the case of butyric acid from 15 mg/gMSO to 197 mg/gMSO, respectively, when using sugarcane filter cake from the Brazilian sugar-energy sector. This suggests that sugarcane filter cake may be an effective substrate due to its rich organic content and favorable fermentation characteristics. On the other hand, CA production from cassava peel was low (0%) under the experimental conditions tested for acid contents, probably due to its limited nutritional composition. These results highlight the potential of sugarcane bagasse as a promising raw material for the sustainable production of AC through AD with methanogenesis inhibition, contributing to the development of renewable energies and bioproducts.